Revitalisasi Nilai-nilai Imago Dei dalam Pembentukan Karakter Anak Pada Era Digital - Paembonan, Yanni; Ronda, Daniel (SOPHIA: Jurnal Teologi dan Pendidikan Kristen, 2024)
The digital era presents new challenges in shaping children's character. Technology, social media, and wide access to information often significantly influence children's mindsets, behaviors, and morality, distancing them from theological principles and Christian teachings. This research explores revitalizing "Imago Dei" in forming children's characters, especially in the increasingly complex digital environment. Christian education not only functions as a transfer of knowledge but also as a medium for restoring the image of God. A qualitative approach was employed using a literature review and field observation of educational practices in Christian schools. The results indicate that the revitalization of the "Imago Dei" can be a solution to counteract the negative effects of the digital era on children's morality and integrity. Emphasizing character formation through Christian values such as love, truth, and justice will strengthen children's ability to reflect the image of God in an increasingly individualistic and materialistic world.  Era digital menghadirkan berbagai tantangan baru dalam pembentukan karakter anak. Teknologi, media sosial, dan akses informasi yang luas seringkali memengaruhi pola pikir, perilaku, dan moralitas anak secara signifikan, menjauhkan anak dari prinsip-prinsip teologi dan ajaran Kristen. Penelitian ini bertujuan untuk merevitalisasi nilai-nilai “Imago Dei” dalam pembentukan karakter anak, khususnya dalam lingkungan digital yang semakin kompleks. Pendidikan Kristen tidak hanya berfungsi sebagai transfer ilmu tetapi juga sebagai transmisi untuk memulihkan citra Allah. Pendekatan kualitatif dengan studi pustaka, observasi lapangan terhadap praktik pendidikan di sekolah-sekolah Kristen. Hasilnya menunjukkan bahwa revitalisasi nilai-nilai “Imago Dei” dapat menjadi solusi untuk menangkal dampak negatif era digital terhadap moralitas dan integritas anak. Penekanan pada pembentukan karakter melalui nilai-nilai Kristen seperti kasih, kebenaran, dan keadilan akan memperkuat kemampuan anak untuk merefleksikan Imago Dei dalam dunia yang semakin individualistis dan materialistis.